2010
DOI: 10.1017/s0007114510001881
|View full text |Cite
|
Sign up to set email alerts
|

Fermented wheat aleurone induces enzymes involved in detoxification of carcinogens and in antioxidative defence in human colon cells

Abstract: Dietary fibre is fermented by the human gut flora resulting mainly in the formation of SCFA, for example, acetate, propionate and butyrate. SCFA, in particular butyrate, may be important for secondary cancer prevention by inducing apoptosis and inhibiting cell growth of cancer cells, thereby inhibiting the promotion and/or progression of cancer. Furthermore, SCFA could also act on primary cancer prevention by activation of detoxifying and antioxidative enzymes. We investigated the effects of fermented wheat al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 52 publications
4
26
0
Order By: Relevance
“…Our results provide evidence that those with ≥ 1 minor allele for the missense polymorphism rs1138272 in GSTP 1 and higher intakes for the categories: total grains and non-whole grains have an increased risk of pancreatic cancer (Table 5). This result is consistent with evidence that dietary fiber intake induces antioxidant/detoxification enzymes including GSTP 1 94 . We observed that those with ≥ 1 minor allele for the gene UGT2 B4 (rs17671289) and intake of dry beans and peas had reduced pancreatic cancer risk (Table 5).…”
Section: Discussionsupporting
confidence: 92%
“…Our results provide evidence that those with ≥ 1 minor allele for the missense polymorphism rs1138272 in GSTP 1 and higher intakes for the categories: total grains and non-whole grains have an increased risk of pancreatic cancer (Table 5). This result is consistent with evidence that dietary fiber intake induces antioxidant/detoxification enzymes including GSTP 1 94 . We observed that those with ≥ 1 minor allele for the gene UGT2 B4 (rs17671289) and intake of dry beans and peas had reduced pancreatic cancer risk (Table 5).…”
Section: Discussionsupporting
confidence: 92%
“…Due to the limited number of samples and large variation range, the incubation of colon adenoma and adenocarcinoma samples with butyrate yielded no significant outcome. Nevertheless, as partly shown by our study and that from Stein et al [43], transformed colon cells respond to butyrate by upregulating CAT expression and/or activity. An increase in CAT activity seems to be desirable since the H 2 O 2 -mediated process of metastasis might be stopped or at least slowed down [44].…”
Section: Discussionsupporting
confidence: 86%
“…In these studies the material was digested in vitro, subsequently followed by in vitro fermentation, after which the fermentation supernatants were exposed to HT29 cells. The results showed that wheat aleurone and aleurone containing whole grain fractions contribute to decreasing colon cancer risk by the reduction of secondary bile acids production, induction of apoptosis, cell differentiation, and detoxification as a result of colon fermentation (Borowicki, 2010;2010a;2010b;Stein et al, 2010;. A very recent work of Ross et al (2011) points to the fact that favorable changes observed in the colonic metabolism of humans after whole grain consumption compared to the consumption of "refined" white flour products are the result of the importance of both fiber and phytochemical components.…”
Section: Cancer Biomarkersmentioning
confidence: 99%